A cure for darkness : the story of depression and how we treat it - Riley, Alex (Science writer) (Scribner, 2021)
What is depression? Is it a persistent low mood or a complex range of symptoms? Is it a single diagnosis or a diversity of mental disorders requiring different treatments? In A Cure for Darkness, science writer Alex Riley explores these questions, digging into the long history of depression and chronicling the lives of psychiatrists and scientists who sought cures for their patients.